2021
DOI: 10.1186/s12979-021-00217-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced immune-regulatory molecule expression on human colonic memory CD4 T cells in older adults

Abstract: Background The etiology of the low-level chronic inflammatory state associated with aging is likely multifactorial, but a number of animal and human studies have implicated a functional decline of the gastrointestinal immune system as a potential driver. Gut tissue-resident memory T cells play critical roles in mediating protective immunity and in maintaining gut homeostasis, yet few studies have investigated the effect of aging on human gut T cell immunity. To determine if aging impacted CD4 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated that both HLA-DR and co-inhibitory molecules regulate innate inflammatory responses in different manners [ 40 42 ]. Since HLA-DR crosslinking can generate intracellular signals to induce TNF-α release in monocytes, enhanced HLA-DR expression is consistent with amplified inflammatory responses in aged monocytes [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that both HLA-DR and co-inhibitory molecules regulate innate inflammatory responses in different manners [ 40 42 ]. Since HLA-DR crosslinking can generate intracellular signals to induce TNF-α release in monocytes, enhanced HLA-DR expression is consistent with amplified inflammatory responses in aged monocytes [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the majority of colonic CD4 T cells are effector memory cells, 44 we also evaluated the expression of GZB in memory and naïve PB CD4 T cell populations (Figure S5). Percentages of naïve (CCR7 + CD45RO − ), central memory (CCR7 + CD45RO + ; CM) and effector memory (CCR7 − CD45RO + ; EM) PB CD4 T cells were generally similar between controls and PWH ( Figure 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, we noted a positive association between frequencies of blood effector memory GZB + CD4 T cells and colonic GZB + CD4 T cells in PWH. Human gut CD4 T cells are mostly composed of effector memory cells, 44 and studies in mice demonstrated that tissue-resident CD8 + T cells can contribute to the circulating memory T cell pool following activation. 45 Thus, the HIV-1-associated increase in blood GZB + CD4 T cells may reflect recently activated gut GZB + CD4 T cells migrating into the systemic circulation rather than differentiation of these cells in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 and CTLA-4, as the inhibitory moleculules, show reduced expression. Also, the expression of Ki67 is decreased, which is associated with steady-state proliferation and renewal of cells ( 63 , 64 ). The inhibitory molecules CTLA-4 and PD-1 can inhibit T cell activation and T cell responses through different mechanisms ( 65 , 66 ).…”
Section: The Impact Of Aging On the Intestinal Immune Systemmentioning
confidence: 99%
“…Also, Ki67 expression is generally low in LP CD4 + T cells from young individuals as well. So, it is difficult to determine the significance of further reduction of Ki67 in aging LP CD4 + T cells ( 63 , 64 ). In addition, aging reduces the frequency and function of LP CD4 Th17 cell, which is important to antigen-specific immune responses and mucosal barrier integrity.…”
Section: The Impact Of Aging On the Intestinal Immune Systemmentioning
confidence: 99%